Key Points and Current Studies on Seepage Theories of Marine Natural Gas Hydrate-Bearing Sediments: A Narrative Review - Peng, Hao; Li, Xiaosen; Chen, Zhaoyang; Zhang, Yu; You, Changyu (Energies, 2022)
The internal fluid flow capacity of hydrate-bearing sediment (HBS) is one of the important factors affecting the efficiency of natural gas exploitation. This paper focuses on seepage studies on gas hydrates with the following contents: scope of theories' application, normalized permeability (K-t) models, extension combined with new technology, and development. No review has elucidated the prediction of original permeability (K-0) of sediments without hydrates. Moreover, there are few studies on seepage theories with new technologies, such as Computed Tomography (CT), Nuclear Magnetic Resonance (NMR), Magnetic Resonance Imaging (MRI), and resistivity. However, this review summarizes the prospects, evolution, and application of HBS seepage theories from the perspectives of experiments, numerical simulation, and microscopic visualization. Finally, we discuss the current limitations and directions of the seepage theories of HBS.